Cinema of discontent : representations of Japan's high-speed growth - Sasaki, Tomoyuki (Albany : State University of New York Press, 2022)
Uses popular films to reveal the tensions generated during Japan's postwar ""economic miracle,"" challenging the prevailing view that it was a story of great national success.
Introduction: Narrating High-Speed Growth through Film -- 1 Drifting in Tokyo: Reconstruction and Uneven Development in Kawashima Yūzō's Susaki Paradise Red Light (1956) -- 2 A Girl from Izu: Labor Migration and Modern Subjectivity in Masumura Yasuzō's Blue-Sky Girl (1957) -- 3 Osaka, City of Spies: The Powerless Worker in Industrial Society in Inoue Akira's Black Weapon (1964) -- 4 Yokohama Romance: The Cold War, Revolution, and Asian Solidarity in Ezaki Mio's A Warm Misty Night (1967) -- 5 Waiting for Spring in Shiretoko: A Postscript to High-Speed Growth in Kumashiro Tatsumi's The Light of Africa (1975)
Includes bibliographical references, index, and filmography.
Online resource title from digital title page; (viewed on January 3, 2023).
JSTOR
Keywords: History in motion pictures; Economics in motion pictures; Motion pictures -- Japan -- History -- 20th century; Japan -- In motion pictures; Performing arts; Video recordings; Electronic books; Histoire au cinéma.; Économie politique au cinéma.; Cinéma -- Japon -- Histoire -- 20e siècle.; Arts du spectacle; Vidéos.; Livres numériques.; performing arts (discipline); video recordings (physical artifacts); e-books.; PERFORMING ARTS / Film & Video / History & Criticism; Economics in motion pictures; History in motion pictures; Motion pictures; Japan; 1900-1999; History